Tarikh a-Lughah al-'Arabiyah Fi Indunisiya - Ahmad Fuad Effendy (The Center for Language Development, Mataram State Islamic University., 2018)
: ?? ????? ?? ???? ??? ????? ?????? ??????????? ?? ?????. ??? ?????